Implementation of functional analysis using value analysis value engineering (VAVE) - Abdullah, Ainul Farahin; Adesta, Erry Yulian Triblas (Asian Research Publishing Network (ARPN), 2015)
This paper presents one of the tools used in Value Analysis Value Engineering (VAVE) methodology; Functional Analysis and its implementation during New Product Development (NPD) phase. Current vehicle outer door handle has been redesigned through its functions in order to meet customer requirements of having higher value vehicle, by increasing performance while trying to decrease the cost without scarifying the quality, saleability and maintainability. An analysis has been made and discussed using Function Analysis System Technique (FAST) diagram to achieve product optimization. Finally, results obtained are discussed.